2016
DOI: 10.1007/s10549-016-3984-8
|View full text |Cite
|
Sign up to set email alerts
|

Young adult breast cancer patients have a poor prognosis independent of prognostic clinicopathological factors: a study from the Japanese Breast Cancer Registry

Abstract: PurposeThe aim of this study was to investigate whether young age at onset of breast cancer is an independent prognostic factor in patients from the Japanese Breast Cancer Registry, after adjustment of known clinicopathological prognostic factors.MethodsOf the 53,670 patients registered between 2004 and 2006 and surveyed after a 5-year follow-up prognosis, 25,898 breast cancer patients (48.3 %), who were obtained prognostic data, were examined. Clinicopathological factors were compared between young adult (YA;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 34 publications
(38 reference statements)
8
44
0
5
Order By: Relevance
“…Overall, our results confirmed the almost universal findings of a worse prognosis for young breast cancer patients, with a higher stage, higher tumor grade, more HR negative tumors [5, 7, 13, 14, 16, 17, 2628]. In other reports, HER2 status was incorporated with hormone receptor negativity to report higher levels of triple-negative tumors [28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, our results confirmed the almost universal findings of a worse prognosis for young breast cancer patients, with a higher stage, higher tumor grade, more HR negative tumors [5, 7, 13, 14, 16, 17, 2628]. In other reports, HER2 status was incorporated with hormone receptor negativity to report higher levels of triple-negative tumors [28].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, a higher percentage of young breast cancer patients are AA; the AA young patients may have more triple-negative tumors and a worse outcome [12, 1922]. Multivariate analyses demonstrated young age as an independent predictor of poor outcome [3, 4, 10, 12, 13, 23] Most published studies are based on a small number of patients and incomplete follow-up. Furthermore, there are potential disparities in treatment and access to care for young women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…These results were consistent with many studies [20,21]. In contrast, several studies concluded that the percentage of patients diagnosed with more advanced stages was higher in the young patients than the older patients [22,23]. While LIN et al [15] concluded that younger patients (< 50 years) were significantly associated with higher frequencies of stage I than older patients (≥ 50 years).…”
Section: Patients Younger Than 40 Years At the Time Of Diagnosis Reprsupporting
confidence: 87%
“…This is in contrast to previous findings, where post-menopausal patients were observed to have better survival whilst younger patients tend to have poor survival. 17,18 Triple-negative breast cancer (TNBC) is a sub-category of breast tumour which lacks the expression of the three most commonly targeted biomarkers considered for breast cancer treatment, namely oestrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor (HER2). 19 TNBC accounts for 15-20% if all breast cancer diagnoses and is usually associated with more aggressive clinical course, worse evolution within the first 3 to 5 years after diagnosis; early and higher rates of distant visceral metastasis compared to other breast cancer subtypes, as well as poor survival.…”
Section: Discussionmentioning
confidence: 99%